Answers to inflation and recession : economic policies for a modern society - Sommers Albert T. (New York : The Conference Board Inc., 1975)
This publication contains the prepared papers submitted to the colloquium, and the comments of the discussants on each paper. Taken together, the documents compose a readable professional appraisal of the procedures for determining and executing U.S. economic policy, and the uncertain and often ambiguous intellectual structure on which the action programs rest.
osa; 15/08/18
Loans
Keywords: Inflation; Recession; Economic policies